Large-Scale Conservation in the Common Interest - Clark, Susan G.; Hohl, Aaron M.; Picard, Catherine H.; Thomas, Elizabeth (Springer Series on Environmental Management,, 2015)
Many people working toward sustainability recognize the important role of conservation but are inadequately prepared to deal with the large spatial, temporal, and complexity scales that are involved in large-scale conservation efforts. Problems in large-scale conservation require navigating an intermixture of geophysical, biological, and political dimensions. Coming to grips with these many natural and human forces and factors at large scales, much less the myriad details in any single case, is challenging in the extreme and becomes more critical with each day that passes.   Large-scale conservation poses many complex challenges that single disciplines, approaches, or methods cannot fully address alone. Interdisciplinarity can significantly strengthen large-scale conservation efforts. Throughout Large-Scale Conservation in the Common Interest the editors and authors argue that a more holistic and genuinely interdisciplinary approach is required to solve the complex and growing challenges associated with large-scale conservation. The chapters within offer such an approach and define key terms, bring challenges to light, and employ case studies to offer concrete practical and strategic recommendations to help those who are engaged in the interactive tasks of promoting sustainability and human dignity.   This book is intended for a broad audience, including students and professors new to the field of large-scale conservation, experienced field-based practitioners in science and management, and decision and policy makers who set specific and strategic direction for large landscapes. Professors can use this book to introduce students to the challenges of successful large-scale conservation design and implementation and to teach interdisciplinarity as a framework, concept, and tool. Professionals will find this book offers a new way of using science, management, and policy to make decisions. Finally, this volume can be used as a guide to set up workshops, seminars, or projects involving diverse people and perspectives.